2019
DOI: 10.1186/s12940-019-0487-1
|View full text |Cite
|
Sign up to set email alerts
|

Relations between air pollution and vascular development in 5-year old children: a cross-sectional study in the Netherlands

Abstract: Background Air pollution has been shown to promote cardiovascular disease in adults. Possible mechanisms include air pollution induced changes in arterial wall function and structure. Atherosclerotic vascular disease is a lifelong process and childhood exposure may play a critical role. We investigated whether air pollution is related to arterial wall changes in 5-year old children. To this aim, we developed an air pollution exposure methodology including time-weighted activity patterns improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Third, when compared with adults, children (0–12 years) have higher metrics with respect to ventilation, absorption, and a higher ratio of body surface to body volume. Therefore, children inhale more air (and air pollution) per unit of body weight [53,54]. Fourth, children spend more time outdoors than adults.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, when compared with adults, children (0–12 years) have higher metrics with respect to ventilation, absorption, and a higher ratio of body surface to body volume. Therefore, children inhale more air (and air pollution) per unit of body weight [53,54]. Fourth, children spend more time outdoors than adults.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Fourth, children spend more time outdoors than adults. Also, due to their lower height, they are exposed to higher concentrations of some pollutants present in the air at lower heights [54]. According to the Barker hypothesis, environmental factors during fetal development and early postnatal life (the first 1000 days of life) may affect the metabolism and development and lead to increased health risks in later life [50,55].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…We found that residential traffic density and exposure to traffic-related NOx in childhood were related to greater changes in CIMT over time. While we previously found no association between traffic-related air pollution in early childhood and CIMT at age 10 years [ 21 ], a limited number of other studies have shown relationships between traffic-related exposures and early cardiovascular changes in children and young adults [ 21 , 36 39 ]. One study found increased carotid artery stiffness among 6–14 year old children living in close proximity (< 300 m) to a highly-trafficked roadway, as compared to those living more than 300 m from the road, while a similar study found that children residing less than 100 m from a busy road had 15% increased CIMT compared to those who lived further from traffic [ 37 , 40 ].…”
Section: Discussionmentioning
confidence: 55%
“…One study found increased carotid artery stiffness among 6–14 year old children living in close proximity (< 300 m) to a highly-trafficked roadway, as compared to those living more than 300 m from the road, while a similar study found that children residing less than 100 m from a busy road had 15% increased CIMT compared to those who lived further from traffic [ 37 , 40 ]. Recent work found that exposures to NO 2 , NO x and PM were associated with decreased distensibility in children at age 5 [ 39 ]. Others have suggested that prenatal and early life may represent sensitive periods for air pollution exposure and cardiovascular health, and have observed associations between prenatal and early air pollution exposures and adverse changes in childhood cardiovascular risk factors, including CIMT, carotid artery stiffness, BP and BMI [ 21 , 22 , 36 , 41 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study in the Netherlands showed that air pollution exposure exerts adverse effects not only in adults but even in children as it determines important arterial wall changes and structure reducing also arterial distensibility in this age of life. 21 More in general, assessing the arterial system, carotid intima media thickness (CIMT), carotid plaques and coronary artery calcification seem to be significantly PM related. 22 …”
Section: Discussionmentioning
confidence: 99%